Rural versus urban healthcare through the lens of health behaviors and access to primary care: a post-hoc analysis of the Romanian health evaluation survey - Lăcrămioara Aurelia Brîndușe; Irina Eclemea; Andrea Elena Neculau; Bogdan Alexandru Păunescu; Eugenia Claudia Bratu; Maria Alexandra Cucu (BMC, 2024)
Abstract Background Worldwide, rural populations are recognized to be exposed to increased health challenges due to their living and working environment, socioeconomic status, and access to health services. According to the Romanian Country Health Profile 2023, approximately 46% of all deaths recorded in Romania in 2019 could be attributed to behavioral risk factors such as tobacco smoking, dietary risks, alcohol consumption and low physical activity. No data on rural versus urban areas are available to date, and research is needed to document health inequalities, identify barriers to health services, and explore solutions. Methods This study is an analysis of data collected during the Health Evaluation Survey carried out by the National Institute of Public Health in 2022 and aimed to reveal differences in health risk factors between rural and urban areas. The analysis was carried out under the methodological framework of the Health Evaluation Survey 2022, which is coordinated by the National Institute of Public Health. Results Our study's objectively measured data revealed that the overall health profile of rural communities is characterized by lower education levels, lower incomes, and higher binge drinking rates than those of their urban counterparts. Additionally, rural inhabitants more often have high blood pressure, are more overweight and obese (per body mass index measurements) and have higher fasting plasma glucose. The health profile of the urban population revealed higher education levels and greater proportions of people with adequate monthly income, people with daily alcohol consumption, people who smoke, and people with hypercholesterolemia. Access to primary health care evaluated through proxy indicators was lower in rural areas but was relatively good overall. Conclusions Our analysis of the health profile of rural communities revealed a greater prevalence of obesity and overweight, especially among women, and an increased prevalence of heavy drinking among men. Access to primary health care evaluated through proxy indicators is lower in rural areas but is relatively good overall. Lower education levels and the possibility of lower health literacy underpin the need for targeted health education campaigns. Sustainable strategies for rural health need to be identified, especially in the field of health promotion and disease prevention programs. Trial registration This study is observational research involving human participants where no interventions were applied to the study population.